PKM Kewirausahaan Diversifikasi Produk Dadar Gulung Menjadi Mini Crepe Roll - Mitha Evalista; Irfan Yunus; Mohamad Ikbal Riski A. Danial; Fitrah Widya Wati; Mas’ud Uqbah Al Ansyari (Lembaga Pengembangan Kinerja Dosen, 2024)
Traditional food is known as market snacks because in the past these snacks were found in many traditional markets. In this modern era, some people consider that omelette rolls are an outdated traditional food or snack. The popularity of rolled omelets is increasingly eroded by modern snacks that are more contemporary and practical. This causes a lack of public interest in omelette rolls, especially the younger generation. This condition is feared to cause the rolled omelette, which is a traditional Indonesian culinary richness, to be forgotten in the future. Therefore, a diversification process must be carried out so that the rolled omelet remains in the market. The process of diversifying omelette rolls as a traditional food into a modern product, namely